Cytokine activin C ameliorates chronic neuropathic pain in peripheral nerve injury rodents by modulating the TRPV1 channel - Huang, Ya‐Kun (Br J Pharmacol, 2020)
BACKGROUND AND PURPOSE: The cytokine activin C is mainly expressed in small‐diameter dorsal root ganglion (DRG) neurons and suppresses inflammatory pain. However, the effects of activin C in neuropathic pain remain elusive. EXPERIMENTAL APPROACH: Male rats and wild‐type and TRPV1 knockout mice with peripheral nerve injury ‐ sciatic nerve axotomy and spinal nerve ligation in rats; chronic constriction injury (CCI) in mice – provided models of chronic neuropathic pain. Ipsilateral lumbar (L)4–5 DRGs were assayed for activin C expression. Chronic neuropathic pain animals were treated with intrathecal or locally pre‐administered activin C or the vehicle. Nociceptive behaviours and pain‐related markers in L4–5 DRGs and spinal cord were evaluated. TRPV1 channel modulation by activin C was measured. KEY RESULTS: Following peripheral nerve injury, expression of activin βC subunit mRNA and activin C protein was markedly up‐regulated in L4–5 DRGs of animals with axotomy, SNL or CCI. [Correction added on 26 November 2020, after first online publication: The preceding sentence has been corrected in this current version.] Intrathecal activin C dose‐dependently inhibited neuropathic pain in spinal nerve ligated rats. Local pre‐administration of activin C decreased neuropathic pain, macrophage infiltration into ipsilateral L4–5 DRGs and microglial reaction in L4–5 spinal cords of mice with CCI. In rat DRG neurons, activin C enhanced capsaicin‐induced TRPV1 currents. Pre‐treatment with activin C reduced capsaicin‐evoked acute hyperalgesia and normalized capsaicin‐evoked persistent hypothermia in mice. Finally, the analgesic effect of activin C was abolished in TRPV1 knockout mice with CCI. CONCLUSION AND IMPLICATIONS: Activin C inhibits neuropathic pain by modulating TRPV1 channels, revealing potential analgesic applications in chronic neuropathic pain therapy.